Preparation method and application of vanadium pentoxide composite carbon material with core-shell structure

By using surface growth technology of vanadium-based alkoxides and metal organic framework particles, the low-cost preparation of core-shell structure V2O5 composite carbon materials is achieved, solving the problems of complex preparation and insufficient electrochemical performance in the prior art, and significantly improving the electrochemical performance of the material.

CN119833323AActive Publication Date: 2025-04-15SHENYANG AEROSPACE UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510023927.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

In the prior art, the preparation of V2O5 is complex and costly, and uniform recombination with carbon materials is difficult to provide sufficient active sites and ion transport channels, affecting electrochemical performance.

Method used

By using vanadium-based alkoxide as the precursor, small-sized metal organic framework (Zn-MI) particles are grown on the surface, and the preparation of core-shell structure V2O5 composite carbon material is achieved through the carbonization process control.

Benefits of technology

It realizes simple and easy control of core-shell structure V2O5 composite carbon material, low cost, and good electrochemical performance, including high specific capacitance and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833323A_ABST
    Figure CN119833323A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of supercapacitors, in particular to a preparation method and application of a vanadium pentoxide composite carbon material with a core-shell structure. Vanadium-based alkoxide is used as a precursor, small-size metal organic framework (Zn-MI) particles grow on the surface of the precursor, and then the core-shell structure V2O5 composite carbon material is prepared by controlling the carbonization process. The metal alkoxide can provide a growth site of Zn-MI due to relatively strong electronegativity of oxygen atoms, and ensures that small-particle Zn-MI grows on the surface of the sphere; and in the carbonization process, the Zn-MI can inhibit the shrinkage of the alkoxide shell layer, so that the preparation of the core-shell V2O5 is realized. In the core-shell structure V2O5 composite carbon material prepared by the invention, the core-shell structure can provide a large number of active sites and slow down the expansion of an electrode charge-discharge structure, and the internal cavity can be used as a place for storing an electrolyte to shorten the transmission distance of ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and in particular to a preparation method and application of a core-shell structured vanadium pentoxide composite carbon material. Background Art

[0002] With the rapid development of high-energy consumption industries, traditional batteries can no longer meet people's needs. Supercapacitors are a new type of energy storage device between traditional capacitors and rechargeable batteries, with excellent electrochemical performance and cycle stability. Supercapacitors, as an electrochemical energy storage device with excellent electrochemical properties, low cost and environmental friendliness, have attracted the attention of more and more scientists and industrial researchers. 2 O 5 Due to its huge energy storage capacity and environmental friendliness, it has been successfully used as a supercapacitor electrode. 2 O 5 Combining with carbon materials can also enhance the conductivity of the composite material and further improve the electrochemical properties. 2 O 5 The structural design can further improve its electrochemical performance. The core-shell structure can provide a large number of active sites to slow down the expansion of the electrode charge and discharge structure, while the internal cavity can be used as a place to store electrolyte to shorten the ion transmission distance. 2 O 5 The preparation of V is relatively complex and difficult. For example, Zeiger et al. (J. Mater. Chem. A, 2016, 4, 18899) synthesized V in situ by a two-step method. 2 O 5 These particles have nano-V 2 O 5 Core V 2 O 5 -C@C core-shell structure, which is completely accessible to electrolyte ions and interconnected by highly conductive carbon, shows excellent specific capacity and cycle stability. However, this method is complicated and cumbersome to operate, and is costly, which is not conducive to practical application. In addition, V 2 O 5 The poor electrical conductivity can be improved by compounding with carbon materials. For example, the commonly used coated carbon is V 2 O 5 The surface is coated with a carbon material with a uniform structure. However, although the conductivity is improved, the carbon material has a charge shielding ability, so this 2 O 5 Homogeneous composite carbon materials usually lack active sites and ion transport channels, which also brings new problems. Summary of the invention

[0003] In view of the problems existing in the prior art, the present invention provides a method for preparing a core-shell structured vanadium pentoxide composite carbon material and its application in a supercapacitor. The preparation method is simple, easy to control, and low in cost, and the prepared material has good electrochemical properties.

[0004] The present invention uses vanadium-based alkoxide as a precursor, grows small-sized metal organic framework (Zn-MI) particles on the surface, and then realizes the core-shell structure V by controlling the carbonization process. 2 O 5 Preparation of composite carbon materials. Metal alkoxides can provide growth sites for Zn-MI due to the strong electronegativity of oxygen atoms, ensuring that small particles of Zn-MI grow on the surface of the sphere; and during the carbonization process, Zn-MI can inhibit the shrinkage of the alkoxide shell, thereby achieving core-shell V 2 O 5 Preparation.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] On the one hand, the present invention provides a core-shell structure V 2 O 5 A method for preparing a composite carbon material, the method comprising the following steps:

[0007] (1) NH 4 VO 3 Dissolve in a mixed solvent of propylene glycol and glycerol, react at 180-200°C for 6-9h, filter, wash and dry to obtain a vanadium alkoxide precursor V-ako;

[0008] (2) The vanadium alkoxide precursor V-ako was reacted with Zn(NO 3 ) 2 6H 2 O was dispersed in methanol and subjected to ultrasound to obtain solution A. 2-Methylimidazole was dissolved in methanol to obtain solution B. Solution B was slowly poured into solution A. The mixed solution was stirred, then filtered, washed, and dried to obtain V-ako@ZIF-8 precursor.

[0009] (3) The V-ako@ZIF-8 precursor was subjected to two high-temperature annealing steps in an argon environment to obtain a core-shell structure V 2 O 5 Composite carbon materials (V 2 O 5 -C@C).

[0010] Furthermore, in step (1), in the mixed solvent of propylene glycol and glycerol, the volume ratio of glycerol to propylene glycol is 2:1 to 8:1.

[0011] Further, in step (1), 0.1-0.65 g NH 4 VO 3 .

[0012] Furthermore, in step (1), the washing is performed using water and ethanol; the drying temperature is 50-70° C., and the drying time is 5-8 h.

[0013] Furthermore, in step (2), the ultrasonication time is 20-30 min.

[0014] Furthermore, in step (2), in the solution A, the concentration of the vanadium alkoxide precursor is 0.0066-0.027 g / ml, and Zn(NO 3 ) 2 6H 2 The concentration of O is 0.013-0.033 g / ml; in the solution B, the concentration of 2-methylimidazole is 0.26-0.46 g / ml; and the stirring time is 1-3 h.

[0015] Furthermore, in step (3), in the two-stage high-temperature annealing, the heating rate of the first stage annealing is 5-10°C / min, the annealing temperature is 600-800°C, and the annealing time is 1-3h, and the heating rate of the second stage annealing is 20-30°C / min, the annealing temperature is 910-1000°C, and the annealing time is 1-3h.

[0016] Another aspect of the present invention provides a core-shell structure V prepared by the above preparation method 2 O 5 Application of composite carbon materials in supercapacitors.

[0017] The principle of the present invention is:

[0018] Metal alkoxides can provide growth sites for Zn-MI due to the strong electronegativity of oxygen atoms, ensuring that small particles of Zn-MI grow on the surface of the sphere. During the carbonization and oxidation process, Zn-MI can inhibit the shrinkage of the alkoxide shell, thereby achieving core-shell V 2 O 5 However, since large-sized Zn-MI particles cannot be grown on the surface of alkoxide, it is impossible to control the core-shell structure.

[0019] The beneficial effects of the present invention are:

[0020] 1) The preparation method of the present invention is simple, controllable and low in cost;

[0021] 2) The core-shell structure V prepared by the present invention 2 O 5In -C@C, the core-shell structure can provide a large number of active sites to slow down the expansion of the electrode charge and discharge structure, while the internal cavity can be used as a place to store electrolyte to shorten the transmission distance of ions;

[0022] 3) V prepared by the present invention 2 O 5 The carbon particles grown on the surface of the composite carbon material can act as protrusions to increase contact with the electrolyte and provide more active sites, while the gaps between particles can serve as transmission channels for the electrolyte, improving the electrochemical performance of the material.

[0023] 4) V prepared by the present invention 2 O 5 Composite carbon materials have good electrical conductivity as well as high specific capacitance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 V prepared in Example 1 2 O 5 SEM images of composite carbon materials;

[0025] Figure 2 V prepared in Example 1 2 O 5 Rate performance diagram of composite carbon materials;

[0026] Figure 3 V prepared in Example 2 2 O 5 Rate performance diagram of composite carbon materials;

[0027] Figure 4 V prepared in Comparative Example 1 2 O 5 -SEM image of C;

[0028] Figure 5 V prepared in Comparative Example 1 2 O 5 -C rate performance diagram. DETAILED DESCRIPTION

[0029] The following examples may enable those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0030] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.

[0031] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0032] Example 1

[0033] (1) 0.1 g NH 4 VO 3 Dissolve in a mixed solvent of 30 ml glycerol and 15 ml propylene glycol, stir at room temperature for 30 min to fully dissolve the solute, transfer into a reactor, react at 180 ° C for 6 h, filter the reaction liquid to obtain the reactant, wash with water and ethanol several times, and dry in an oven at 50 ° C for 8 h to obtain a spherical product vanadium alkoxide (V-ako);

[0034] (2) 0.1 g V-ako and 0.2 g Zn(NO 3 ) 2 6H 2 O was dispersed in 15 ml of methanol and ultrasonically treated for 20 min to form solution A. 3.9 g of 2-methylimidazole was dissolved in 15 ml of methanol to form solution B. Solution B was slowly poured into solution A. The mixed solution was stirred for 1 h, then filtered, washed and dried to obtain V-ako@ZIF-8 precursor.

[0035] (3) 0.15 g of V-ako@ZIF-8 was subjected to two high-temperature annealing steps in an argon environment. The first annealing step had a heating rate of 5 °C / min, an annealing temperature of 600 °C, and an annealing time of 1 h. The second annealing step had a heating rate of 20 °C / min, an annealing temperature of 910 °C, and an annealing time of 1 h. V 2 O 5 -C@C.

[0036] The compound is in 1Ag -1 The specific capacitance is 530F / g. -1 Unit, the ratio is 68%.

[0037] Example 2

[0038] (1) 0.65 g NH 4 VO 3 Dissolve in a mixed solvent of 35 ml glycerol and 10 ml propylene glycol, stir at room temperature for 40 min to fully dissolve the solute, transfer into a reactor, react at 200 ° C for 9 h, filter the reaction liquid to obtain the reactant, wash with water and ethanol several times, and dry in an oven at 70 ° C for 5 h to obtain a spherical product vanadium alkoxide (V-ako);

[0039] (2) 0.3 g V-ako and 0.5 g Zn(NO 3 ) 2 6H 2O was dispersed in 15 ml of methanol and ultrasonically treated for 30 min to form solution A, then 6.9 g of 2-methylimidazole was dissolved in 15 ml of methanol to form solution B, solution B was slowly poured into solution A, the mixed solution was stirred for 3 h, and then filtered, washed and dried to obtain V-ako@ZIF-8 precursor;

[0040] (3) 0.5 g of V-ako@ZIF-8 was subjected to two high-temperature annealing steps in an argon environment. The first annealing step had a heating rate of 10 °C / min, an annealing temperature of 800 °C, and an annealing time of 2 h. The second annealing step had a heating rate of 30 °C / min, an annealing temperature of 1000 °C, and an annealing time of 1 h. V 2 O 5 -C@C.

[0041] The compound is in 1Ag -1 The specific capacitance is 508F / g. -1 Unit, the ratio is 63.2%.

[0042] Example 3

[0043] (1) 0.35 g NH 4 VO 3 Dissolve in a mixed solvent of 35 ml glycerol and 10 ml propylene glycol, stir at room temperature for 30 min to fully dissolve the solute, transfer into a reactor, react at 200 ° C for 9 h, filter the reaction liquid to obtain the reactant, wash with water and ethanol several times, and dry in an oven at 70 ° C for 5 h to obtain a spherical product vanadium alkoxide (V-ako);

[0044] (2) 0.4 g V-ako and 0.3 g Zn(NO 3 ) 2 6H 2 O was dispersed in 15 ml of methanol and ultrasonically treated for 30 min to form solution A. Then 5.9 g of 2-methylimidazole was dissolved in 15 ml of methanol to form solution B, which was slowly poured into solution A. The mixed solution was stirred for 2 h, and then filtered, washed and dried to obtain V-ako@ZIF-8 precursor;

[0045] (3) 0.4 g of V-ako@ZIF-8 was subjected to two high-temperature annealing steps in an argon environment. The first annealing step had a heating rate of 8 °C / min, an annealing temperature of 700 °C, and an annealing time of 3 h. The second annealing step had a heating rate of 20 °C / min, an annealing temperature of 950 °C, and an annealing time of 2 h. V 2 O 5 -C@C.

[0046] The compound is in 1Ag -1The specific capacitance is 454F / g. -1 Unit, the ratio is 66.4%.

[0047] Example 4

[0048] (1) 0.65 g NH 4 VO 3 Dissolve in a mixed solvent of 35 ml glycerol and 10 ml propylene glycol, stir at room temperature for 40 min to fully dissolve the solute, transfer into a reactor, react at 200 ° C for 9 h, filter the reaction liquid to obtain the reactant, wash with water and ethanol several times, and dry in an oven at 70 ° C for 5 h to obtain a spherical product vanadium alkoxide (V-ako);

[0049] (2) 0.3 g V-ako and 0.5 g Zn(NO 3 ) 2 6H 2 O was dispersed in 15 ml of methanol and ultrasonically treated for 30 min to form solution A. Then 4.9 g of 2-methylimidazole was dissolved in 15 ml of methanol to form solution B. Solution B was slowly poured into solution A. The mixed solution was stirred for 2 h, and then filtered, washed and dried to obtain V-ako@ZIF-8 precursor.

[0050] (3) 0.5 g of V-ako@ZIF-8 was subjected to two high-temperature annealing steps in an argon environment. The first annealing step had a heating rate of 5 °C / min, an annealing temperature of 700 °C, and an annealing time of 1 h. The second annealing step had a heating rate of 25 °C / min, an annealing temperature of 950 °C, and an annealing time of 2 h. V 2 O 5 -C@C.

[0051] The compound is in 1Ag -1 The specific capacitance is 473F / g. -1 Unit, the ratio is 62.5%.

[0052] Example 5

[0053] (1) 0.55 g NH 4 VO 3 Dissolve in a mixed solvent of 40 ml glycerol and 5 ml propylene glycol, stir at room temperature for 30 min to fully dissolve the solute, transfer into a reactor, react at 180 ° C for 9 h, filter the reaction liquid to obtain the reactant, wash with water and ethanol several times, and dry in an oven at 70 ° C for 5 h to obtain a spherical product vanadium alcohol salt (V-ako);

[0054] (2) 0.3 g V-ako and 0.5 g Zn(NO 3 )2 6H 2 O was dispersed in 15 ml of methanol and ultrasonically treated for 30 min to form solution A, then 6.3 g of 2-methylimidazole was dissolved in 15 ml of methanol to form solution B, solution B was slowly poured into solution A, the mixed solution was stirred for 2 h, and then filtered, washed and dried to obtain V-ako@ZIF-8 precursor;

[0055] (3) 0.5 g of V-ako@ZIF-8 was subjected to two high-temperature annealing steps in an argon environment. The first annealing step had a heating rate of 5 °C / min, an annealing temperature of 800 °C, and an annealing time of 1 h. The second annealing step had a heating rate of 20 °C / min, an annealing temperature of 980 °C, and an annealing time of 3 h. V 2 O 5 -C@C.

[0056] The compound is in 1Ag -1 The specific capacitance is 480F / g. -1 Unit, the ratio is 67.2%.

[0057] Example 6

[0058] (1) 0.35 g NH 4 VO 3 Dissolve in a mixed solvent of 35 ml glycerol and 10 ml propylene glycol, stir at room temperature for 40 min to fully dissolve the solute, transfer into a reactor, react at 190 ° C for 9 h, filter the reaction liquid to obtain the reactant, wash with water and ethanol several times, and dry in an oven at 70 ° C for 5 h to obtain a spherical product vanadium alkoxide (V-ako);

[0059] (2) 0.3 g V-ako and 0.5 g Zn(NO 3 ) 2 6H 2 O was dispersed in 15 ml of methanol and ultrasonically treated for 30 min to form solution A, then 3.9 g of 2-methylimidazole was dissolved in 15 ml of methanol to form solution B, solution B was slowly poured into solution A, the mixed solution was stirred for 3 h, and then filtered, washed and dried to obtain V-ako@ZIF-8 precursor;

[0060] (3) 0.3 g of V-ako@ZIF-8 was subjected to two high-temperature annealing steps in an argon environment. The first annealing step had a heating rate of 5 °C / min, an annealing temperature of 600 °C, and an annealing time of 3 h. The second annealing step had a heating rate of 25 °C / min, an annealing temperature of 910 °C, and an annealing time of 3 h. V 2 O 5 -C@C.

[0061] The compound is in 1A g -1 The specific capacitance is 440F / g. -1 Unit, the ratio is 66.5%.

[0062] Example 7

[0063] (1) 0.3 g NH 4 VO 3 Dissolve in a mixed solvent of 35 ml glycerol and 10 ml propylene glycol, stir at room temperature for 30 min to fully dissolve the solute, transfer into a reactor, react at 200 ° C for 6 h, filter the reaction liquid to obtain the reactant, wash with water and ethanol several times, and dry in an oven at 60 ° C for 5 h to obtain a spherical product vanadium alkoxide (V-ako);

[0064] (2) 0.3 g V-ako and 0.5 g Zn(NO 3 ) 2 6H 2 O was dispersed in 15 ml of methanol and ultrasonically treated for 30 min to form solution A. Then 5.9 g of 2-methylimidazole was dissolved in 15 ml of methanol to form solution B. Solution B was slowly poured into solution A. The mixed solution was stirred for 1 h and then filtered, washed and dried to obtain V-ako@ZIF-8 precursor.

[0065] (3) 0.5 g of V-ako@ZIF-8 was subjected to two high-temperature annealing steps in an argon environment. The first annealing step was performed at a heating rate of 10 °C / min, an annealing temperature of 650 °C, and an annealing time of 3 h. The second annealing step was performed at a heating rate of 20 °C / min, an annealing temperature of 910 °C, and an annealing time of 1 h. V 2 O 5 -C@C.

[0066] The compound is in 1Ag -1 The specific capacitance is 380F / g. -1 Unit, the ratio is 61.2%.

[0067] Comparative Example 1

[0068] (1) 0.1 g NH 4 VO 3 Dissolve in a mixed solvent of 30 ml glycerol and 15 ml propylene glycol, stir at room temperature for 30 min to fully dissolve the solute, transfer into a reactor, react at 180 ° C for 6 h, filter the reaction liquid to obtain the reactant, wash with water and ethanol several times, and dry in an oven at 50 ° C for 8 h to obtain a spherical product vanadium alkoxide (V-ako);

[0069] (2) 0.15 g of V-ako was subjected to two high-temperature annealing steps in an argon environment. The first annealing step had a heating rate of 5 °C / min, an annealing temperature of 600 °C, and an annealing time of 1 h. The second annealing step had a heating rate of 20 °C / min, an annealing temperature of 910 °C, and an annealing time of 1 h. The fragmented structure V 2 O 5 -C.

[0070] The compound is in 1Ag -1 The specific capacitance is 150F / g. -1 Unit, the ratio is 45.2%.

[0071] Comparative Example 1 shows that no core-shell structure V is formed after annealing without ZIF-8 coating. 2 O 5 -C@C, the rate and specific capacitance of the formed product are not ideal.

[0072] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a core-shell structure V2O5 composite carbon material, characterized in that: The method comprises the following steps: (1) dissolving NH4VO3 in a mixed solvent of propylene glycol and glycerol, reacting at 180-200°C for 6-9h, filtering, washing, and drying to obtain a vanadium alkoxide precursor V-ako; (2) Dispersing the vanadium alkoxide precursor V-ako and Zn(NO3)2·6H2O in methanol, ultrasonicating to obtain solution A, dissolving 2-methylimidazole in methanol to obtain solution B, slowly pouring solution B into solution A, stirring the mixed solution, and then filtering, washing, and drying the mixed solution to obtain V-ako@ZIF-8 precursor; (3) The V-ako@ZIF-8 precursor was subjected to two stages of high-temperature annealing in an argon environment to obtain a core-shell structured V2O5 composite carbon material.

2. The method for preparing the core-shell structure V2O5 composite carbon material according to claim 1, characterized in that: In step (1), in the mixed solvent of propylene glycol and glycerol, the volume ratio of glycerol to propylene glycol is 2:1 to 8:

1.

3. The method for preparing the core-shell structure V2O5 composite carbon material according to claim 1, characterized in that: In step (1), 0.1-0.65 g NH4VO3 is dissolved in every 45 ml of the mixed solvent.

4. The method for preparing the core-shell structure V2O5 composite carbon material according to claim 1, characterized in that: In step (1), the washing is performed by washing with water and ethanol; The drying temperature is 50-70° C., and the drying time is 5-8 hours.

5. The method for preparing the core-shell structure V2O5 composite carbon material according to claim 1, characterized in that: In step (2), the ultrasonic time is 20-30 minutes.

6. The method for preparing the core-shell structure V2O5 composite carbon material according to claim 1, characterized in that: In step (2), in the solution A, the concentration of the vanadium alkoxide precursor is 0.0066-0.027 g / ml, and the concentration of Zn(NO3)2·6H2O is 0.013-0.033 g / ml; In the solution B, the concentration of 2-methylimidazole is 0.26-0.46 g / ml; The stirring time is 1-3h.

7. The method for preparing the core-shell structure V2O5 composite carbon material according to claim 1, characterized in that: In step (3), in the two-stage high-temperature annealing, the heating rate of the first stage annealing is 5-10°C / min, the annealing temperature is 600-800°C, and the annealing time is 1-3h, and the heating rate of the second stage annealing is 20-30°C / min, the annealing temperature is 910-1000°C, and the annealing time is 1-3h.

8. Use of the core-shell structured V2O5 composite carbon material prepared by the preparation method according to any one of claims 1 to 7 in a supercapacitor.

Citation Information

Patent Citations

  • Method of dispersing nanoparticles, core-shell-structured nanoparticles, preparation method of same, and lubricant oil

    CN107488483A

  • Preparation method and application of lithium ion battery negative electrode material

    CN108550834A

  • Preparation method and application of V2O5 / C composite nanosheet material

    CN111446442A

  • 3D printing zinc vanadate / carbon nano composite electrode and preparation method and application thereof

    CN117524740A

  • KR20240116871A